New approaches of visualising the problematic suburban developments: Based on a comparative analysis of the “Urban Sprawl” discussion in the US and Germany - Wolf, Sabine; Hagedorn, Carsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
The article presents new ways of visualising problematic suburban developments. After reflecting on the dealing with peripheral growth in the US and Germany, possible future developments of space in an exemplary region are simulated by means of computer graphics. The advantage of this process lies in the number of different graphical results in one scenario after accessing the system. There is no firm development stipulated. Rather, different possible developments are shown.